Community Empowerment through Training in Progressive Muscle Relaxation Therapy Skills to Lower Blood Pressure in Hypertension Patients in Ayula Selatan Village - Wenny Ino Ischak; Fakhriatul Falah; Ratnawati Ratnawati; Kartin Buheli (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Hypertension is the most common non Hypertension is recorded as one of the cardiovascular diseases with the highest number of sufferers in Gorontalo, and is a global health issue. An increase in blood pressure that is not controlled will cause various dangerous complications such as disorders of the kidneys, heart and brain. To prevent complications, it is necessary to carry out non-pharmacological interventions in addition to pharmacological therapy as an effort to control blood pressure in hypertensive patients in the long term. Progressive muscle relaxation is an independent treatment option that can help hypertensive patients control their blood pressure. The purpose of this community service is to empower health cadres to increase community knowledge and skills in applying progressive muscle relaxation therapy as an effort to control blood pressure. Activities in this community service consist of forming a group of health cadres caring for hypertension who are trained in progressive relaxation therapy, then followed by assisting the cadres in providing education to the target community for hypertension sufferers. Evaluation of this activity was carried out by measuring the knowledge of cadres through data analysis from filling out questionnaires and measuring the blood pressure of hypertension sufferers. By the results of the pretest and posttest it was found that there was an increase in knowledge of 50% in health cadres and there was a decrease in systolic blood pressure of 29 mmHg and a decrease in systolic blood pressure of 12 mmHg in hypertensive subjects. From the results of this activity it can be implied that the application of progressive muscle relaxation can be used as alternatice intervention to control blood pressure in hypertensive patients as home care.